Network Virtualization Interconnection Technology - Sai Ma; Hui Huang; Shijun Xia; Yaohui Jin; Xuan Luo (Dianxin kexue)
Industry and the Academia have carried out various kinds of network virtualization technologies to cope with the growing requirement of cloud network. The diversity in network virtualization technologies wi11 lead to the co-existence of various kinds of technologies in cloud environment. However，the differences among network virtualization technologies separate the overa11 network resources into several isolated“islands”. In order to solve the problem，a solution called network virtualization interconnection technology was introduced. The key challenges of realizing the interconnection were discussed，then a novel software defined networking based interconnection architecture Omni-Bridge was proposed. Finally，a prototype of Omni-Bridge was introduced and a functional validation experiment was presented.